Accessibility of fitness facilities and physical activity participation: a comparison of disabled athletes and disabled people / Ellail Ain Mohd Aznan... [et al.] - Mohd Aznan, Ellail Ain; Ismail, Ahmad Dzulkarnain; Mohd Kassim, Ahmad Fikri; Md Yusof, Mohd Khairulanwar; Samat, Hajar Asmidar (Universiti Teknologi MARA, Perlis, 2022)
Accessibility is one of the most important aspects of the open environment, as it provides a sense of freedom, competence, and autonomy for active involvement and use. However, there is still a question about the accessibility given at sports and fitness facilities, particularly for disabled individuals, which has a negative impact on their involvement in physical activity. The purpose of this study was to investigate an association between the accessibility of fitness facilities and the engagement of impaired people and athletes in physical exercise. The participants in this study were divided into two groups: disabled persons (N=50) and disabled athletes (N=50), totalling 100 people with disabilities. The Accessibility Instrument Measuring Fitness and Recreation Environments (AIMFREE) and the Physical Activity Scale for Individuals with Physical Disabilities (PASID) were used to evaluate accessibility and physical participation (PASIPD). The Independent Sample t-test was used to examine the outcome. The findings revealed a significant relationship between fitness facility accessibility and physical activity involvement (p0.01, r=0.356**) and a significant difference in physical activity participation between disabled persons and disabled athletes (p<0.05). The findings demonstrated that the accessibility of fitness facilities has an impact on the amount of physical activity engagement and that disabled athletes are more attached to physical activity than disabled persons. The research might be broadened to learn more about the factors that influence disparities in physical activity engagement among impaired athletes and disabled persons